USING THE HEALTH EQUITY FRAMEWORK TO EXPLORE DISPARITIES IN THE MANAGEMENT OF CHILDHOOD LANGUAGE DISORDERS IN IBADAN: AN EXPLORATORY STUDY. - Salako, Ibraheem (Student’s Journal of Health Research Africa, 2023)
Introduction: Children with language disorders are underserved and do not attract the required attention given their impact on health and broader life outcomes. Research guided by public health frameworks is needed to identify the spheres of influence that determine health outcomes. This study explored the determinants of health behaviors that dictate outcomes in children with language disorders using the Health Equity Framework (HEF). Methods: This qualitative study analyzed 36 semi-structured interviews among Speech-Language-therapists, teachers, and parents of children with language disorders using inductive coding and content analysis. Results: The paper examined health disparities in managing children with language disorders using the HEF, with all domains of the HEF being represented. The absence of systems of power leads to unfair access to necessary resources and opportunities for the promotion of health outcomes in children with language disorders. Family, kin, and communities play important roles in shaping health actions that can either promote or inhibit the fair distribution of services to these children. The cumulative experiences of seeking intervention and parental response to the social, behavioral, and environmental conditions contribute to health outcomes in children with language disorders. Conclusion: Findings indicate that the HEF offers a structured approach to understanding health disparities in children with language disorders, emphasizing the requirement for policy and process development to address context-related determinants of such disparities. This can guide and establish standards for management processes aimed at eliminating preventable health outcome discrepancies among children with language disorders in Nigeria. Recommendation: To promote health equity among children with language disorders, policymakers should use the Health Equity Framework to identify and address the factors that contribute to health disparities. Taking a comprehensive approach that considers the interplay of the HEF domains is crucial for developing effective interventions that ensure all children have equal opportunities to achieve good health.